THE PRE-ANALYTICAL STAGE OF LABORATORY DIAGNOSTICS AND ITS IMPACT ON THE RELIABILITY OF RESULTS - Karimova Gulhayo,; Nurmatova M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Laboratory diagnostics is an integral part of modern clinical medicine and plays a key role in diagnosis, monitoring disease progression, and evaluating the effectiveness of therapy. According to various studies, up to 70–80% of clinical decisions are made based on laboratory test results, which underscores their high diagnostic significance [1]. In this regard, ensuring the reliability and reproducibility of laboratory results is one of the priority tasks of the healthcare system. The laboratory process is traditionally divided into three main stages: pre-analytical, analytical, and post-analytical. Despite the active development of analytical technologies and the automation of laboratory tests, it is the pre-analytical stage that remains the most vulnerable link in laboratory diagnostics [2]. According to the World Health Organization and the International Federation of Clinical Chemistry (IFCC), up to 60–70% of all laboratory errors occur at the pre-analytical stage [3].The pre-analytical stage covers all processes preceding the actual analysis of the sample, including the appointment of the study, preparation of the patient, collection of biological material, its labeling, transportation, storage, and preparation for analysis [4]. Errors made at any of these stages can lead to distorted laboratory results, false positive or false negative results, and, as a consequence, to erroneous clinical decisions [5]. With the introduction of high-precision automated analyzers, the importance of the preanalytical stage not only remains unchanged but also increases, since analytical systems are unable to compensate for errors made before the start of the test [6]. This determines the relevance of a comprehensive study of the factors of the preanalytical stage and their impact on the reliability of laboratory results.